PENGEMBANGAN KEPRIBADIAN GURU PAI DI ERA DIGITAL DAN IMPLIKASINYA TERHADAP KETELADANAN MORAL SISWA - Halida, Fierly Noer; Siti Fauziah Rahmah; Dede Nurul Mustopa S; Mursidin (STKIP Subang, 2026)
This study seeks to examine the development of personality competence among Islamic Religious Education (PAI) teachers in the digital era and its impact on students’ moral exemplarity. The research applies a library research approach by reviewing various credible academic sources, including journals, books, and indexed scholarly publications. Data collection was conducted through documentation, while data analysis employed content analysis and literature synthesis techniques. The results reveal that strengthening teachers’ personality must be rooted in solid spiritual values, digital ethics, and adaptive digital literacy. Teachers who exhibit integrity, emotional stability, and responsible conduct in digital environments can function as effective moral role models for students. In line with social cognitive theory, students are inclined to imitate behaviors demonstrated by teachers, both in face-to-face and virtual interactions. In conclusion, the personality competence of PAI teachers holds a significant role in shaping students’ moral character, particularly in fostering discipline, ethical digital behavior, and religious awareness in the digital age.